Why Don’t You Go to Bed on Time? A Daily Diary Study on the Relationships between Chronotype, Self-Control Resources and the Phenomenon of Bedtime Procrastination - Kühnel, Jana; Syrek, Christine J.; Dreher, Anne (Frontiers in Psychology, 2018)
Background: This daily diary study investigates the phenomenon of bedtime procrastination. Bedtime procrastination is defined as going to bed later than intended, without having external reasons for doing so. We highlight the role chronotype (interindividual differences in biological preferences for sleep-wake-times) plays for bedtime procrastination. Moreover, we challenge the view that bedtime procrastination is the result of a lack of self-regulatory resources by investigating momentary self-regulatory resources as a predictor of day-specific bedtime procrastination. Methods: One-hundred and eight employees working in various industries completed a general electronic questionnaire (to assess chronotype and trait self-control) and two daily electronic questionnaires (to assess momentary self-regulatory resources before going to bed and day-specific bedtime procrastination) over the course of five work days, resulting in 399 pairs of matched day-next-day measurements. Results: Results of multilevel regression analyses showed that later chronotypes (also referred to as evening types or ‘owls’) tended to report more bedtime procrastination on work days. Moreover, for late chronotypes, day-specific bedtime procrastination declined over the course of the work week. This pattern is in line with expectations derived from chronobiology and could not be explained by trait self-control. In addition, on evenings on which employees had less self-regulatory resources available before going to bed—compared to evenings on which they had more self-regulatory resources available before going to bed—employees showed lower bedtime procrastination. This finding contradicts the prevailing idea that bedtime procrastination is the result of a lack of self-regulatory resources. Conclusions: The findings of this study provide important implications for how bedtime procrastination should be positioned in the field of procrastination as self-regulatory failure and for how bedtime procrastination should be dealt with in practice.